Analysis of the Village Revenue and Expenditure Budget Administration Accounting System (APBDes) in Ulak Paceh Village - Eka Sevtia Mesta; Ryan Al Rachmat (Penerbit Jurnal Indonesia, 2022)
This study aims to produce a model of the village accounting administration system to be applied in villages in accordance with government laws and regulations. The result of this study is the Village Accounting Administration Procedure to be used in villages in Indonesia as an administrative guideline.. The research data analysis technique is collecting data from observation interviews and documentation and then the data is used as material for system and procedure analysis. The results of this study found that Ulak Paceh village accounting administration employees need to learn the laws and government regulations when administering village accounting. With their limited competence in the field of accounting and administration, this administrative activity is very difficult for them. With the analysis of the APBDes administrative accounting system in Ulak Paceh village, it is hoped that administrative activities in Ulak Paceh village will be better than before.